Rapid Catalytic Water Disinfection from Earth Abundant Ca2Fe2O5 Brownmillerite. (12th September 2021) - Vanags, Mārtiņš; Mežule, Linda; Spule, Arnita; Kostjukovs, Juris; Šmits, Krišjānis; Tamm, Aile; Juhna, Talis; Vihodceva, Svetlana; Käämbre, Tanel; Baumane, Larisa; Začs, Dzintars; Vasiliev, Grigory; et al.
Abstract: Water disinfection is a crucial challenge for humanity. Approaches that are effective, cheap, environmentally friendly, and do not promote gene exchange between bacteria are urgently required. Strongly oxidizing radicals are highly promising to achieve this as they lead to bacterial activation at high efficiencies. However, sources to consistently generate these radicals are limited to high energy UV/H2 O2 treatments requiring a large energy input. Here the use of abundant, cheap, brownmillerite (Ca2 Fe2 O5 ) is demonstrated as an efficient radical generation material under dark conditions, showing a seven order of magnitude decrease in bacterial concentration over 10 min. This decrease is attributed to the release of interlayer Ca 2+ from the layered structure of Ca2 Fe2 O5 and hydroxyl radical generation. The efficacy of Ca2 Fe2 O5 is demonstrated by disinfecting turbid sewage sludge. The identification of this cheap, abundant, and nontoxic antibacterial material will provide an opportunity for broad scale clean water generation globally, and address the United Nations' Sustainable Development Goal of clean water and sanitation. Abstract : Disinfection of water is paramount for humanity. By simply adding an earth abundant, cheap mineral, Ca2 Fe2 O5, to sewage sludge, the bacterial concentration is reduced by four orders of magnitude. Using controlled, laboratory samples an eight order of magnitude decrease is achieved in just 30 min, attributed to the structural transformation and subsequent radical release from Ca2 Fe2 O5 .